Acoustic performance of architected hybrid metamaterials for sound attenuation applications. (October 2022) - Medhin, Yacob; Khan, Kamran A
Acoustic insulators in sound attenuation applications usually have a structure with a characteristic dimensions equivalent to the operating wavelength, posing significant challenges in low-frequency sound attenuation applications. Recent advancements in material science, advanced materials called acoustic metamaterials (AMMs) have paved the way for designing efficient noise insulation passive and active devices. This paper proposes heterogeneous integrated passive metamaterials for enhanced sound insulation in broad frequency bands. Six acoustic meta-unit cells (UCs) with deep subwavelength thickness were proposed and analyzed numerically for the acoustic band structure and transmission characteristics. Out of these six UCs, three high-performing UCs were chosen for further analysis. Finite element (FE) analysis results showed that the maximum transmission loss conforms with the computed band structures. Next, we proposed several heterogeneous meta-structures consisting of different combinations of chosen meta-unit cells. The FE analysis results showed that a broader band of sound absorptions can be achieved through the hybrid design of AMMs. Our research revealed that the suggested structures may be utilized to create metamaterials with a wider absorption band, making them suitable for a variety of applications.